2013
DOI: 10.3402/dfa.v4i0.22487
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic and functional results in the treatment of early stages of Charcot neuroarthropathy with a walker boot and immediate weight bearing

Abstract: BackgroundOne of the most common gold standards for the treatment of Charcot neuroarthropathy (CN) in the early Eichenholtz stages I and II is immobilization with the total contact casting and lower limb offloading. However, the total amount of offloading is still debatable.ObjectivesThis study evaluates the clinical and radiographic findings in the treatment of early stages of CN (Eichenholtz stages I and II) with a walker boot and immediate total weight-bearing status.MethodsTwenty-two patients with type 2 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(41 citation statements)
references
References 15 publications
0
40
0
1
Order By: Relevance
“…Three non‐controlled studies concluded that a non‐removable TCC or walker boot can be effective and safe for weight‐bearing treatment to prevent ulcers in acute Charcot's neuro‐osteoarthropathy .…”
Section: Ulcer Preventionmentioning
confidence: 99%
“…Three non‐controlled studies concluded that a non‐removable TCC or walker boot can be effective and safe for weight‐bearing treatment to prevent ulcers in acute Charcot's neuro‐osteoarthropathy .…”
Section: Ulcer Preventionmentioning
confidence: 99%
“…Depth of the ulceration as well as presence of an infection and/or ischemia are key factors to predict the risk of amputation according to the well-accepted Wagner/Armstrong classification [7,8]. The incidence of Charcot neuropathy among diabetic patients is reported to be up to 7.5% [9,10]. Foot ulcers are the most common foot problem in diabetic patients [3] and are often associated with Charcot neuropathy or osteomyelitis [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…11,[21][22][23][24][25]38 In the second group, the study's primary aim was to report outcomes of CN but they may also describe monitoring techniques used, thus providing data to answer our fifth objective on whether monitoring techniques influence outcomes. [6][7][8][9][10][12][13][14][15][16][26][27][28][29][30][31][32][33][34][35][36][37] 3.3 | Techniques used in the monitoring of CN Armstrong et al 38 Level 3…”
Section: Study and Participant Characteristicsmentioning
confidence: 99%